2021
DOI: 10.1016/j.celrep.2021.109883
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor signaling regulates metabolic pathways critical to myeloid-derived suppressor cell function within the TME

Abstract: Highlights d Tumor progression increases the expression of b2-AR on MDSCs d b2-AR signaling increases fatty acid oxidation and oxidative phosphorylation in MDSCs d b2-AR signaling in MDSCs increases autophagy-mediated PGE2 production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 59 publications
(74 reference statements)
0
47
0
Order By: Relevance
“…Approaches to target dysfunctional lipid metabolism show prospects (Bian et al, 2021). Recent studies also have mentioned the regulation among NRGs, immune response, and cellular metabolism (Jensen et al, 2021;Mohammadpour et al, 2021;Wan et al, 2021). Apart from Frontiers in Cell and Developmental Biology frontiersin.org that, drug prediction revealed that benzimidazole-related and vinca-alkaloid-related drugs could effectively reverse these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to target dysfunctional lipid metabolism show prospects (Bian et al, 2021). Recent studies also have mentioned the regulation among NRGs, immune response, and cellular metabolism (Jensen et al, 2021;Mohammadpour et al, 2021;Wan et al, 2021). Apart from Frontiers in Cell and Developmental Biology frontiersin.org that, drug prediction revealed that benzimidazole-related and vinca-alkaloid-related drugs could effectively reverse these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, carnitine palmitoyltransferase 1a (CPT1a) + VIDCAI + DR − M-MDSC expansion was observed in patients with severe COVID-19 ( 73 ). CPT1a is involved in fatty acid oxidation and has been correlated with the recruitment and differentiation of MDSCs ( 77 ).…”
Section: Mdscs and Covid-19mentioning
confidence: 99%
“…Experimental model systems have identified the β 2 -adrenergic pathway to be implicated in the physiological effects of stress on cancer progression. 62 , 97 , 98 , 206 - 209 Epidemiological studies in cancer patients that compared use of cardio selective versus non-selective β-blockade found a favorable effect of non-selective β-blockade. 189 , 200 Another important issue is the potential for confounding in non-randomized observational research where indication for β-blocker use is correlated with many diseases that are likely to adversely impact cancer progression.…”
Section: Pharmacologic Approaches To Reduce Stress-related Cancer Pro...mentioning
confidence: 99%